Website for Good Governance: Inside the Public Communication and Engagement of DPRKP Kabupaten Serang - Raden Ayu Gisti Sasti Putri; Tri Nuraniwati (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
This study aims to analyze the use of DPRKP Kab. Serang’s website as a media for public communication and how it is implemented to establish good governance. Good governance refers to a set of principles and practices that contribute to the effective and responsible management of public affairs. It emphasizes that government actions are clearly communicated to the public. This study applied descriptive qualitative study by conducting direct observation, literature study related to media publication in government institutions and good governance and in-depth interviews with 45 respondents. The result of this study showed that the use of DPRKP Kab. Serang’s website as a media for publication served as a platform for public communication for information dissemination. Thus, the implementation of good governance in DPRKP Kab. Serang’s website is generally good. Good governance principles have been implemented such as participation, transparency, accountability, effectiveness and efficiency